Influence of vacuum on diffusion of moisture inside seeds of cereals - В.А. Швидя; С.П. Степаненко; Б.И. Котов; А.В. Спирин; В.Ю. Кучерук (Қарағанды университетінің хабаршысы. Физика сериясы)
The article solves the problem of thermal injury of seeds of grain crops during drying, which are capillaryporous bodies. It is hypothesized that the use of a vacuum in the drying chamber reduces the risk of thermal stress. In this regard, the article studies the effect of a vacuum inside the drying chamber on the diffusion of moisture inside the seeds. Seeds are complex materials in which moisture has different bonds with dry matter. During the working process, the drying speed in the surface layers and inside the seeds occurs at different speeds. As a result, drying stresses occur, which cause cracks on the surface of the seeds. Based on the solution to the differential diffusion equation with an absorbing screen as a boundary condition, the condition for drying without thermal stresses is found. Experimental verification of theoretical studies is carried out on a specially made experimental setup on the example of corn seeds. The effect of thermal stress on seed viability is determined by laboratory germination. Experimental studies confirm the adequacy of theoretical statements. Thus, when drying the seeds of grain crops, which are capillary-porous bodies, there is a limit value of rarefaction, above which cracks appear on the surface of the seeds due to different drying rates on the surface and inside. For drying seeds of grain crops without thermal stresses, it is necessary to consider not only the heating temperature but also the rarefaction in the drying chamber, which should be close to the limit value.